Insights into biological functions across species: examining the role of Rab proteins in YIP1 family function. (1st August 2005) - Chen, C.Z.; Collins, R.N.
Abstract : The YIP1 family comprises an evolutionarily conserved group of membrane proteins, which share the ability to bind di-prenylated Rab proteins. The biochemical capability of YIP1 family proteins suggests a possible role in the cycle of physical localization of Rab proteins between their cognate membranes and the cytosol. YIP1 is essential for viability in yeast and a deletion of YIP1 can be rescued with the human homologue YIP1A. We have made use of this evolutionary conservation of function to generate a series of mutant alleles of YIP1 to investigate the biological role of Yip1p. Our findings indicate evidence for the participation of Yip1p in both Rab and COPII protein function; at present, we are not able to distinguish between the models that these roles represent, i.e. independent or dependent activities of Yip1p.